FPGA Implementation of a Nakagami-m fading channel Simulator using Random Number Generator - Santhosh Kumar B; K. Ayyappa Swamy (Institute of Advanced Engineering and Science, 2016)
By realizing the concept of implementation of the radio propagation channels on simulators is the eminent intention of this work. Even though prototyping software simulators are effortless to design we prefer hardware simulators as they endeavors distinguishable quickness, compared to earlier. Prior to this work fading channels like Gaussian, Rayleigh and Rician fading channel simulators were executed on hard ware.(i.e. FPGA) The significant target of this attempt is to implement Nakagami-m fading channel on hardware as they preserved for unsubstantial consideration. While differentiating with other fading channels Nakagami-m fading channel acquires wide spread applications, as its capability of providing appropriate fit for practical fading data, as this is flexible through its size parameter ‘m’, over which representation of signal fading conditions that vary from serious to modest, to normal fading or no fading is accomplished . The proposed hardware simulator can hatches complex Nakagami variates after it was implemented on XilinxSpartan-xc3s500e-4fg320 FPGA. This is operated at 50MHz.